Disinvestment of central and state enterprises: Analysis and way ahead - Dhameja, Nand (2003)
The clock on Public Sector Undertaking has taken the full turn. Once seen as the engines of industrial growth, most of the state enterprises became a big drain on public money a decade or so later. The economic reforms of 1991-92 initiated the steps for privatisation or sale of such units on the economic grounds so as to lessen the burden on government finances. The article analyses the strategy, economics and administrative exercise behind the process of disinvestment. It provides a profile of the nature of enterprises and the financial gains to the government. The conclusion discusses the progress made so far and what lies ahead on the road to privatisation and disinvestment. - Reproduced.
Keywords: Privatization - India; Public sector - India; Privatization